Factors influencing the performance of organocatalysts immobilised on solid supports: A review - Fehér, Zsuzsanna; Richter, Dóra; Dargó, Gyula; Kupai, József (Beilstein Journal of Organic Chemistry, 2024)
Organocatalysis has become a powerful tool in synthetic chemistry, providing a cost-effective alternative to traditional catalytic methods. The immobilisation of organocatalysts offers the potential to increase catalyst reusability and efficiency in organic reactions. This article reviews the key parameters that influence the effectiveness of immobilised organocatalysts, including the type of support, immobilisation techniques and the resulting interactions. In addition, the influence of these factors on catalytic activity, selectivity and recyclability is discussed, providing an insight into optimising the performance of immobilised organocatalysts for practical applications in organic chemistry.
Keywords: asymmetric synthesis; catalyst recycling; heterogenisation; organocatalysis; solid support